Depression and associated factors among infertile women at Tu Du hospital, Vietnam: a cross-sectional study - Vo TM; Tran QTT; Le CV; Do TTH; Le TM (Dove Medical Press, 2019)
Tuan M Vo,1 Quynh TT Tran,2 Cuong V Le,3 Trang TH Do,4 Thi M Le51Department of Obstetrics and Gynecology, University of Medicine and Pharmacy at Ho Chi Minh City, Ho Chi Minh City, Vietnam; 2Department of General Gynecology, Tu Du Hospital, Ho Chi Minh City, Vietnam; 3The Science and Technology Office, University of Medicine and Pharmacy at Ho Chi Minh City, Ho Chi Minh City, Vietnam; 4Department of Disaster Management, Hanoi University of Public Health, Hanoi, Vietnam; 5Department of Population and Reproductive Health, Hanoi University of Public Health, Hanoi, VietnamBackground: About 40,000 infertile couples visit Tu Du Hospital, Vietnam for consultation and treatment of infertility per year. Depression in infertile female patients not only influences mental wellbeing, but also affects the effectiveness of infertility treatment. The study aimed to determine the depression prevalence in infertile female patients and associated factors.Methods: A cross-sectional study was conducted during April–July 2016 with 401 infertile women visiting the Department of Infertility at Tu Du Hospital . The PHQ-9 scale was used to measure depressive symptoms. Face-to-face interviewing was conducted using a structured questionaire. Participants were also inquired about demographic characteristics, socio-economic status, infertility related characteristics and family and social relationships.Results: The depression prevalence was 12.2%, with a cut-off score ≥10 on PHQ-9 scale. Depression in infertile female patients was associated with infertility caused by the husband (AOR=3.09, 95% CI=1.44–6.63), infertility caused by both spouses (AOR=3.63, 95% CI=1.26–10.48), alcohol-addicted husband (AOR=4.83, 95% CI=1.32–17.58), and with wife’s previous antidepressant use (AOR=48.1, 95% CI=4.83–47.96)Conclusions: Assessment of depressive symptoms should be assessed at an early stage among infertile female patients for timely mental health support.Keywords: infertile female patient, depression, PHQ-9